A Comprehensive Review of QAM-OFDM Optical Networks - Dhingra, A; Kumar, S; Payal, Payal; Sharma, D; Dahiya, S (International Journal of Computer Sciences and Engineering, 2025)
Orthogonal Frequency Division Multiplexing (OFDM) is a FDM scheme that has the ability to cope with harsh channel conditions without using complex equalization filters. With the introduction of guard band, OFDM offers better orthogonality for the transmission channels affected by high frequency attenuations in copper wire, frequency selective fading and Narrow-Band (NB) interference due to multipath propagation. Each subcarrier is modulated employing a digital modulation scheme such as Quadrature Amplitude Modulation (QAM) with lower symbol rate in order to achieve higher data rates in comparison to single carrier modulation scheme for the given bandwidth. We have studied QAM-OFDM based optical networks in order to obtain higher data rates with lower Bit Error Rate (BER). Variants of OFDM have also been discussed along with its advantages and limitations to achieve the desired optimum performance in the optical networks. This paper presents a detailed study of M-ary QAM OFDM schemes and methods used to overcome effects of Inter Symbol Interference (ISI) and Inter Carrier Interference (ICI) with optimum utilization of system bandwidth